PETER JAMES & PETER G. VAN DER VEEN (eds.), Solomon and Shishak. Current Perspectives from Archaeology, Epigraphy, History and Chronology. Proceedings of the Third BICANE Colloquium held at Sidney Sussex College, Cambridge 26–27 March, 2011. BAR International Series 2732. Oxford, Archaeopress, 2015. xii + 281. ISBN 978–1–4073–1389–4. £47.00 - Tebes, Juan Manuel (2015)
Fil: Tebes, Juan Manuel. Pontificia Universidad Católica Argentina; Argentina